Electrografted monolayer based on a naphthalene diimide–ruthenium terpyridine complex dyad: efficient creation of large-area molecular junctions with high current densities. Issue 80 (7th September 2017) - Frath, Denis; Nguyen, Van Quyen; Lafolet, Frédéric; Martin, Pascal; Lacroix, Jean-Christophe
Abstract : Robust monolayers with multiple redox states were used to create large-area molecular junctions (MJ) with a high yield of operating devices. These MJs show high current densities and rectifications properties. Abstract : An electron donor–acceptor dyad has been designed for the creation of large-area molecular junctions (MJ). Diazonium cation electrografting was used to form well controlled monolayers. The robustness of the monolayer enabled the creation of MJs using direct top-coat evaporation with a high yield of operating devices.